1993
DOI: 10.1002/j.1460-2075.1993.tb06212.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of intronic boundaries is required for the second splicing step efficiency of a group II intron.

Abstract: Group II and nuclear pre-mRNAs introns share a common splicing pathway involving a lariat intennediate, as well as some primary sequence similarities at the splice junctions.In this work, we analyze the role of the conserved nucleotides at the first and penultimate positions (Gl and A886) of a group II self-splicing intron.We show that the Gi nucleotide is essential for the efficiency of both the first and the second splicing steps, while substitutions at the penultimate nucleotide affect mostly the efficiency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(43 citation statements)
references
References 34 publications
2
41
0
Order By: Relevance
“…The ⌬GA mutation dramatically inhibits the trans splicing reaction, and the DM abolishes splicing under transesterification conditions+ Note, however, that the splicing defects of all four substrates (including DM) are partially rescued under hydrolysis conditions (data not shown)+ For this set of experiments, we also confirmed that the D5 G3U and ⌬GA mutations do not exert their ef- -7), and the control was incubated for 120 min (lane 8)+ D: Same as C, except the DM RNA was the substrate+ fects by increasing the reversal of the second step of splicing (data not shown)+ Whether group II introns harbor one or two catalytic sites is a matter of debate+ If group II introns harbor two distinct catalytic sites, then one might expect to find certain intron nucleotides that are essential for the first step of splicing and other nucleotides that are essential for the second step+ This topic was reviewed by Michel and Ferat (1995), who concluded that no evidence exists indicating that any particular group II intron nucleotide participates in catalysis of only one of the two steps of splicing+ Although the fact remains that no intron nucleotide has been found to participate exclusively in only one of the two steps of splicing, our results with the ⌬GA mutation are particularly striking in this regard+ Point mutations that primarily affect the second step of group II intron splicing are rare+ Furthermore, to see the effects of such mutations on the second step of splicing, it is typically necessary to study the mutations in the context of a precursor with a short (13 nt) 59 exon (Jacquier & Michel, 1990;Jacquier & Jacquesson-Breuleux, 1991;Chanfreau & Jacquier, 1993)+ The short precursor is used because, even in the absence of point mutations, the second step of splicing is known to be slow when short transcripts are used+ In the past, the effects of second-step specific mutations have only been seen in the context of the short precursor+ In contrast, we find that even in the context of the full-length precursor, the ⌬GA mutation dramatically slows the second step of splicing+ Thus, to our knowledge, the ⌬GA mutation has the most dramatic effect on the second step of splicing of any point mutation that has been studied+ Why does deletion of the GA dinucleotide specifically slow the second step of splicing? We have recently found that group II introns can be released by an alternative pathway that results in release of the intron as a true circle in which the first residue of the intron is joined to the last residue by a 29-59 phosphodiester bond (H+L+ Murray et al+, submitted)+ We hypothesized that the ⌬GA mutation slows the second step of splicing because it stimulates the use of the terminal uridine residue of the intron as an alternative branch site and that, when the alternative branch site is used, the second step of splicing is inhibited+ However, primer extension analysis of the intron/E3 intermediate showed no evidence that the terminal uridine is used as an alternative branch site in the mutant substrate (data not shown)+ As an alternative model, we considered the possibility that the ⌬GA mutation inhibits the conformational change that has been shown to occur between the first and second steps of splicing+ The conformational change was first described by Chanfreau and Jacquier (1996), who showed that mutations that block the conformational change also speed the reversal of the first step of splicing + As described above, we find that the ⌬GA mutation does not speed the reversal of the first step of splicing+ Thus, it is unlikely that the mutation affec...…”
Section: Effect Of Point Mutations On the Second Step Of Splicingmentioning
confidence: 94%
“…The ⌬GA mutation dramatically inhibits the trans splicing reaction, and the DM abolishes splicing under transesterification conditions+ Note, however, that the splicing defects of all four substrates (including DM) are partially rescued under hydrolysis conditions (data not shown)+ For this set of experiments, we also confirmed that the D5 G3U and ⌬GA mutations do not exert their ef- -7), and the control was incubated for 120 min (lane 8)+ D: Same as C, except the DM RNA was the substrate+ fects by increasing the reversal of the second step of splicing (data not shown)+ Whether group II introns harbor one or two catalytic sites is a matter of debate+ If group II introns harbor two distinct catalytic sites, then one might expect to find certain intron nucleotides that are essential for the first step of splicing and other nucleotides that are essential for the second step+ This topic was reviewed by Michel and Ferat (1995), who concluded that no evidence exists indicating that any particular group II intron nucleotide participates in catalysis of only one of the two steps of splicing+ Although the fact remains that no intron nucleotide has been found to participate exclusively in only one of the two steps of splicing, our results with the ⌬GA mutation are particularly striking in this regard+ Point mutations that primarily affect the second step of group II intron splicing are rare+ Furthermore, to see the effects of such mutations on the second step of splicing, it is typically necessary to study the mutations in the context of a precursor with a short (13 nt) 59 exon (Jacquier & Michel, 1990;Jacquier & Jacquesson-Breuleux, 1991;Chanfreau & Jacquier, 1993)+ The short precursor is used because, even in the absence of point mutations, the second step of splicing is known to be slow when short transcripts are used+ In the past, the effects of second-step specific mutations have only been seen in the context of the short precursor+ In contrast, we find that even in the context of the full-length precursor, the ⌬GA mutation dramatically slows the second step of splicing+ Thus, to our knowledge, the ⌬GA mutation has the most dramatic effect on the second step of splicing of any point mutation that has been studied+ Why does deletion of the GA dinucleotide specifically slow the second step of splicing? We have recently found that group II introns can be released by an alternative pathway that results in release of the intron as a true circle in which the first residue of the intron is joined to the last residue by a 29-59 phosphodiester bond (H+L+ Murray et al+, submitted)+ We hypothesized that the ⌬GA mutation slows the second step of splicing because it stimulates the use of the terminal uridine residue of the intron as an alternative branch site and that, when the alternative branch site is used, the second step of splicing is inhibited+ However, primer extension analysis of the intron/E3 intermediate showed no evidence that the terminal uridine is used as an alternative branch site in the mutant substrate (data not shown)+ As an alternative model, we considered the possibility that the ⌬GA mutation inhibits the conformational change that has been shown to occur between the first and second steps of splicing+ The conformational change was first described by Chanfreau and Jacquier (1996), who showed that mutations that block the conformational change also speed the reversal of the first step of splicing + As described above, we find that the ⌬GA mutation does not speed the reversal of the first step of splicing+ Thus, it is unlikely that the mutation affec...…”
Section: Effect Of Point Mutations On the Second Step Of Splicingmentioning
confidence: 94%
“…The 8-8' interaction consists of a base pair between the nucleotide immediately upstream of the EBS1 sequence and the first nucleotide of the 3' exon (Jacquier and Jacquesson-Breuleux, 1991); these nucleotides are designated by + symbols. Empty triangles indicate an interaction between the first and penultimate nucleotides of the intron (Chanfreau and Jacquier, 1993 (Tuerk et al, 1988) the intron excised as a lariat and the ligated exons, as the normal aiSy reaction. As shown in Figure 6, our (aSAID + ID) system is reactive and most probably proceeds through the same reaction pathway as the normal, monomolecular self-splicing reaction, since reaction products with the expected electrophoretic mobilities are obtained.…”
Section: P1-p2 Substratementioning
confidence: 99%
“…Unlike the case of the terminal G residues, no combinations of 5 0 and 3 0 mutations of the U and A residues restored function (Ruis et al 1994). Nevertheless, the potential for an A-U base pair interaction obviously exists and similar interactions appear to play a role in splicing of group II autocatalytic introns (Chanfreau and Jacquier 1993). We therefore investigated possible interactions of these nucleotides in the U12-dependent system by comparing the effects of single and double mutations of the penultimate intron nucleotides.…”
Section: Introductionmentioning
confidence: 99%